Clinical effectiveness and cost-effectiveness of prehospital intravenous fluids in trauma patients. - Dretzke, J; Sandercock, J; Bayliss, S; Burls, A (2004)
OBJECTIVES: To systematically review the evidence on the effectiveness (in terms of mortality and morbidity) of prehospital intravenous (i.v.) fluid replacement, compared with no i.v. fluid replacement or delayed fluid replacement, in trauma patients with no head injury who have haemorrhage-induced hypotension due to trauma. DATA SOURCES: Electronic databases, relevant websites, handsearching, expert contacts. REVIEW METHODS: Search strategies were defined to identify randomised controlled trials (RCTs) and previous systematic reviews relating to the use of i.v. fluids in a prehospital (or other) setting compared to no fluids or delayed fluids. Inclusion and exclusion criteria were applied to identified studies, and key quality criteria of included studies were checked. Data were extracted independently by two reviewers. Economic evaluations were also systematically sought and appraised. RESULTS: Four relevant RCTs were identified, three of which were poorly designed and/or conducted. One good-quality RCT suggested that i.v. fluids may be harmful in patients with penetrating injuries. No evidence was found on the relative effectiveness of i.v. fluids in patients with blunt versus penetrating trauma. No reliable evidence was found from systematic reviews to suggest that a particular type of fluid is more beneficial compared to another type, although there was a trend favouring crystalloids over colloids. The relative costs of using i.v. fluids versus not using them were found to be very similar and changes in the use of fluids would therefore have no cost consequences for the ambulance service. A more detailed cost-effectiveness analysis would require further information on the relative consequences (mortality, morbidity) of different resuscitation strategies. CONCLUSIONS: The review found no evidence to suggest that prehospital i.v. fluid resuscitation is beneficial, and some evidence that it may be harmful. This evidence is however not conclusive, particularly for blunt trauma. A UK Consensus Statement, and to a lesser extent the UK Joint Royal Colleges Ambulance Liaison Committee guidelines represent a more cautious approach to fluid management than previously advocated and are therefore consistent with the limited evidence base. Further research is required on hypotensive (cautious) resuscitation versus delayed or no fluid replacement, particularly in blunt trauma. There is also a need for an improvement in the quality of data collection and analysis of routinely collected ambulance call-out data.